2014
DOI: 10.1530/eje-14-0172
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in diurnal rhythmicity in patients treated for nonfunctioning pituitary macroadenoma: a controlled study and literature review

Abstract: Objective: Patients treated for nonfunctioning pituitary macroadenomas (NFMAs) have fatigue and alterations in sleep characteristics and sleep-wake rhythmicity frequently. As NFMAs often compress the optic chiasm, these complaints might be related to dysfunction of the adjacent suprachiasmatic nucleus (SCN). We aimed to explore whether indirect indices of SCN functioning are altered in the long term after surgery for NFMAs. Methods: We studied 17 NFMA patients in long-term remission after transsphenoidal surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Data collection from patients and HCPs revealed a wide range of symptoms and needs experienced by the participating patient groups. This is in line with previous research addressing the impact of living with chronic health conditions [1][2][3][4][37][38][39][40][41][42]. Patients with chronic health conditions are characterized by large individual variations in symptoms, symptom frequency, symptom severity and the degree to which the patients are bothered by the symptoms, which makes it difficult to anticipate the type of care that may be in the patients' best interest.…”
Section: Describing Patients' Current Situationsupporting
confidence: 84%
See 2 more Smart Citations
“…Data collection from patients and HCPs revealed a wide range of symptoms and needs experienced by the participating patient groups. This is in line with previous research addressing the impact of living with chronic health conditions [1][2][3][4][37][38][39][40][41][42]. Patients with chronic health conditions are characterized by large individual variations in symptoms, symptom frequency, symptom severity and the degree to which the patients are bothered by the symptoms, which makes it difficult to anticipate the type of care that may be in the patients' best interest.…”
Section: Describing Patients' Current Situationsupporting
confidence: 84%
“…They had to be ≥18 years old and able to read and speak Norwegian. Both patient groups frequently experience a long period of slow deterioration of their health status before undergoing surgery, and both groups do experience a variety of symptoms in the aftermath [36][37][38][39][40], which negatively impact HRQoL [41,42]. Renal replacement therapy through RTX is generally accepted as the preferred treatment for end-stage renal disease [36].…”
Section: Settings and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human autopsied pituitaries, PER1 mRNA expression showed daytimedependent differences according to time of death with decreased levels observed at evening, whereas the protein levels of PER1, CRY1 and CLOCK did not fluctuate with the time of day (Becquet et al 2014). In other studies, circadian rhythmicity has been indirectly studied through melatonin secretion and sleep disturbances (Joustra et al 2014). Altered melatonin secretion was found in 41% of patients with non-functional pituitary macroadenomas (NFPA) (Joustra et al 2014); those patients had high daytime levels, no evening rise or severe irregularity of melatonin secretion.…”
Section: Clock Genes and Pituitary Neoplasmsmentioning
confidence: 99%
“…1 In sighted subjects, most cases remains idiopathic, but few studies reported CRSWD in patients with hypothalamic lesions, namely tumors, and postsurgical or actinic lesions. [2][3][4] The role of pineal gland lesions in causing FRD is controversial. 5,6 FRD is not listed among the pineal cyst-related symptoms, which encompass instead headache, visual disturbances, vertigo, vomiting, and other sleep-related complaints.…”
Section: Introductionmentioning
confidence: 99%